2014
DOI: 10.1523/jneurosci.2400-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Restraint Stress Alters Nociceptin/Orphanin FQ and CRF Systems in the Rat Central Amygdala: Significance for Anxiety-Like Behaviors

Abstract: Corticotropin releasing factor (CRF) is the primary mediator of stress responses, and nociceptin/orphanin FQ (N/OFQ) plays an important role in the modulation of these stress responses. Thus, in this multidisciplinary study, we explored the relationship between the N/OFQ and the CRF systems in response to stress. Using in situ hybridization (ISH), we assessed the effect of body restraint stress on the gene expression of CRF and N/OFQ-related genes in various subdivisions of the amygdala, a critical brain struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 36 publications
1
80
1
Order By: Relevance
“…These rats showed that NPS specifically exerts anxiolytic effects on msP rats. A similar phenomenon was previously observed for drugs such as nociception agonists and CRF1 receptor antagonists; both classes of compounds possess marked anxiolytic effects and reduced alcohol drinking in msP rats but not in heterogeneous Wistar rats (Ayanwuyi et al 2013; Ciccocioppo et al 2014; de Guglielmo et al 2015; Gehlert et al 2007). Most importantly, our finding agrees with previous studies published in genetically selected alcohol-preferring P rats, in which ICV administration of NPS attenuated home cage alcohol drinking and elicited a marked anxiolytic effect (Badia-Elder et al 2008).…”
Section: Discussionsupporting
confidence: 81%
“…These rats showed that NPS specifically exerts anxiolytic effects on msP rats. A similar phenomenon was previously observed for drugs such as nociception agonists and CRF1 receptor antagonists; both classes of compounds possess marked anxiolytic effects and reduced alcohol drinking in msP rats but not in heterogeneous Wistar rats (Ayanwuyi et al 2013; Ciccocioppo et al 2014; de Guglielmo et al 2015; Gehlert et al 2007). Most importantly, our finding agrees with previous studies published in genetically selected alcohol-preferring P rats, in which ICV administration of NPS attenuated home cage alcohol drinking and elicited a marked anxiolytic effect (Badia-Elder et al 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, acute and chronic stress induces differential changes in the ppNN/OFQ expression, with their decreased expression in the central amygdala in response to acute stressor and increased expression in the bed nucleus and reticular thalamus in response to a repeated restraint stressor (Delaney et al, 2012). Injection of N/OFQ in the central nucleus of amygdala is shown to significantly and selectively reduce anxiety-like behavior (in the elevated plus maze test) in restraint rats, suggesting that acute stress activates the N/OFQ system in this brain region to produce anti-stress effects (Ciccocioppo et al, 2014). In response to acute restraint stress, the enhanced expression of N/OFQ in the CA1, CA3, and dentate gyrus of the hippocampus and rise in the plasma corticosterone levels has been documented.…”
Section: Role Of Nociceptin On Stress-related Behaviormentioning
confidence: 99%
“…Furthermore, because AT 1a R and CRF are both expressed in moderate levels in the CeA (Ciccocioppo et al, 2014, Shekhar et al, 2005, Von Bohlen Und Halbach and Albrecht, 1998b) and PVN (Premer et al, 2013, Aguilera et al, 1995a), we expected that this knockout would be pronounced in these areas.…”
Section: Introductionmentioning
confidence: 99%